Advanced research methodology: introduction to the study of complex systems and its applications. part vii: studies on gene interaction (epistasis and machine learning) - Costa, Lucas; Argibay, Pablo (Revista del Hospital Italiano de Buenos Aires, 2014)
In medicine, there are few genetic diseases that can be explained by the presence of a monogenic disorder, rather it is in the complex interactions of genes and extragenic factors where we can find the molecular underpinnings of some diseases. Epistasis is the phenomenon of interaction of genes, resulting in a particular phenotypic trait, behavior or molecular process related, inter alia with various diseases. It is a complex phenomenon and is currently part of the analysis that aims to link the combinatorial interaction of genes with a particular disease. A machine learning method, called multifactor dimensionality reduction (MDR) is presented as an interesting alternative to traditional parametric methods for detecting and characterizing nonlinear interactions among genes